Agro-Biochemical Based Characterization And Molecular Profiling Of Linseed (Linum Usitattissimum L.) Cultivars (Applied Biological Research, 2018)
Nineteen commercial cultivars of flax (Linum usitatissimum L.) were subjected  to genetic diversity analysis, fingerprinting and identification of informative  marker allele(s) for seed purity assessment based on agro-morphological and biochemical quality traits and inter simple sequence repeat (ISSR) marker. A  total of 74 reproducible bands ranged from 120 to 1200 bp were amplified out  of which 68 were polymorphic among the cultivars. Dendrogram constructed  showed no clear grouping of cultivars with regard to the parentage/pedigree  record and breeding centres. The 2D plot obtained with PCA analysis clearly  supported the results obtained by cluster analysis. Further, ISSR profiling helped in the identification of 15 genotypes by cultivar specific bands. The  findings of this study would provide a useful guide for selecting specific  cultivar with a desirable agronomic trait with distinct genetic background for  linseed breeding program in India.
Keywords: Agro-biochemical characterization; fatty acid; fingerprinting; ISSR markers; linseed